MENURUNNYA PRESTASI AKADEMIS MAHASISWA AKUNTANSI PADA PEMBELAJARAN DARING DI MASA PANDEMI COVID-19 - Hasan Ashari; Trinandari Prasetya Nugrahanti (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2022)
This study aims to try to find out what factors influenced student achievement in e-learning during the Covid-19 Pandemic along with Government policies requiring daring learning in tertiary institutions. Daring learning carried out through daring has many limitations, both in terms of faculty and student factors. This research is a descriptive study with a quantitative approach. The primary data source in this study was obtained through a questionnaire. The population in this study were accounting students throughout Indonesia with a sample size of 1087 students randomly in the cities of Java, Sumatra and Madura. This study found that there was a reduced application of learning methods, increased student difficulty, daring learning facilities and infrastructure were not optimal, and daring learning did not benefit students, which in turn led to decreased academic achievement. In this study it was concluded that the factors that influence student academic achievement are the learning design, technical tools in daring learning and the ability of students to carry out individual learning